Modeling Changes in the In-Migration Patterns of Northern Saskatchewan Communities : a Log-Linear Approach - Murauskas, G.; Green, Milford; Bone, Robert (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1986)
This paper examines changes in the historical pattern of in-migration to small frontier communities in northern Saskatchewan in three time periods: 1927-1960, 1961-1970 and 1971-1976. The problems associated with spatial interaction modeling in a developing or frontier region are noted, particularly the low volume of in-migration and the inappropriateness of mass terms as surrogate measures of nodal attractiveness and propulsiveness. As an alternative, a log-linear approach is adopted, whereby multidimensional contingency-table analysis of categorical data reveals structural components in the spatial-interaction process. Initial results indicate that the gender of the migrant has no effect on the propensity to migrate and that spatial patterns of in-migration have not changed over time.